Ischemia-Modified Albumin: Could It Be a New Oxidative Stress Biomarker for Colorectal Carcinoma? - Ellidag, Hamit Yasar (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2013)
BACKGROUND/AIMS: An impaired oxidative/antioxidative status plays an important role in the pathogenesis of many diseases, including cancer. The aim of this study was to evaluate the levels of the novel marker ischemia-modified albumin (IMA) and albumin-adjusted IMA (Adj-IMA) in patients with colorectal cancer (CRC) and look for the associations of these with the total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI). METHODS: Forty patients with CRC (19 females and 21 males; mean age, 56.5±2.1 years) and 39 age- and sex-matched healthy people (22 females and 17 males; mean age, 56.0±1.7 years) were included in this study. Serum levels of IMA, TAS, and TOS were analyzed, and the OSI was calculated. RESULTS: Serum IMA, TOS, and OSI levels were significantly higher in patients with CRC than in controls (p<0.0001), whereas TAS levels were significantly lower in CRC patients (p=0.03). There was no significant difference in serum Adj-IMA levels between groups (p=0.32). CONCLUSIONS: In this study, the oxidative/antioxidant status was impaired in favor of oxidative stress in CRC patients. This observation was not confirmed by IMA measurement. Further studies are needed to establish the relationship between IMA and oxidative stress parameters in CRC and other cancers.